Characteristics of belching, swallowing, and gastroesophageal reflux in belching patients based on Rome III criteria. Issue 8 (22nd July 2013) - Li, Jianbo; Xiao, Yinglian; Peng, Sui; Lin, Jinkun; Chen, Minhu
Abstract Background and Aims Belching is a common disorder with undetermined pathogenesis. With the combined multichannel intraluminal impedance pH monitoring, two different models of belching have been defined: gastric belching (GB) and supragastric belching (SB). The aim of this study was to assess whether SB was associated with air swallowing as compared with GB or healthy volunteers based on Rome III criteria. Methods Consecutive patients who presented with troublesome repetitive belching were recruited. Both upper endoscopy and multichannel intraluminal impedance pH monitoring were performed. Patients were divided into two groups: SB and GB groups according to the percentage of the predominant belching types. Twenty volunteers were enrolled as healthy controls. The number of air swallowing, regular swallowing, and gastroesophageal reflux profile was compared among the three groups. Results Thirty‐seven patients were included in the study: 25 in the SB group and 12 in GB group. SB patients presented more belching events than GB patients (P < 0.05). There were no significant differences among the SB, GB patients, and healthy volunteers concerning the episodes of air swallowing and regular swallowing (P > 0.05). No significant difference was found among the three groups in regard with the reflux parameters (P > 0.05). The number of gas‐containing reflux episodes were 33.0 (20.0, 48.0), 39.5 (29.5, 47.5), and 30.5 (27.0, 41.8) among SB, GB, and healthy volunteers (P = 0.383), respectively. Conclusions SB patients presented with more belching events compared with GB patients. However, air swallowing and reflux profile were similar among the SB, GB patients, and normal controls.